A case of severe acute respiratory syndrome coronavirus 2 with acute thrombotic cerebral infarction and generalized thrombosis (Indian Journal of Case Reports, 2021)
The full spectrum of coronavirus disease 2019 (COVID-19) has not been fully described yet. COVID-19 is associated with a high risk of thrombotic complications such as venous thromboembolism and cerebrovascular disease. Here, we report an autopsy case of a 55-year-old woman diagnosed with severe viral pneumonia complicated by acute cerebral infarction and venous and arterial thrombosis in different organs. The patient died due to severe acute respiratory syndrome coronavirus 2. Macroscopically and histologically, in addition to viral pneumonia and diffuse hemorrhages, fibrin clots were found in arteries and venous vessels of medium and large size in the brain, lungs, and pancreas. Propagation of cerebrovascular thrombosis has led to extensive cerebral infarction. The dating of this infarction, according to the macroscopical findings and the histological changes, was between 24 and 48 h before death. This case confirms the hypothesis on the risk of generalized arterial and venous thromboses in coronavirus infection.